The Confessional Situation and Social Stability - Babinov, Jurij A.; Petrova, Ludmila N. (Univerzita Pardubice, 2007)
Gaining state independence in 1991 and the rejection of the totalitarian political and economic systems stipulated quite a new situation in the life of the Ukrainian society. It has naturally lead to a dynamic development of religious organizations and of church life as the greatly increased number of religious centers, monasteries, religious study centers, religious periodicals and publications well illustrates. Religious variety in the modern Ukrainian society has a set of problems concerning the relations between confessions.
Keywords: contemporary Ukraine; religious variety; social life; religious organizations